Factors Associated with Outpatient Therapy Utilization in Extremely Preterm Infants - Ponnapakkam, Adharsh; Carr, Nicholas R.; Comstock, Bryan A.; Perez, Krystle; O'Shea, T. Michael; Tolia, Veeral N.; Clark, Reese H.; Heagerty, Patrick J.; Juul, Sandra E.; Ahmad, Kaashif A.; for the Preterm Erythropoietin Neuroprotection Trial Consortium (American Journal of Perinatology, 2021)
Objective Factors influencing utilization of outpatient interventional therapies for extremely low gestational age newborns (ELGANs) after discharge remain poorly characterized, despite a significant risk of neurodevelopmental impairment. We sought to assess the effects of maternal, infant, and environmental characteristics on outpatient therapy utilization in the first 2 years after discharge using data from the Preterm Erythropoietin Neuroprotection (PENUT) Trial.Study Design This is a secondary analysis of 818, 24 to 27 weeks gestation infants enrolled in the PENUT trial who survived through discharge and completed at least one follow-up call or in-person visit between 4 and 24 months of age. Utilization of a state early intervention (EI) program, physical therapy (PT), occupational therapy (OT), and speech therapy (ST) was recorded. Odds ratios and cumulative frequency curves for resource utilization were calculated for patient characteristics adjusting for gestational age, treatment group, and birth weight.Results EI was not accessed by 37% of infants, and 18% did not use any service (PT/OT/ST/EI). Infants diagnosed with severe morbidities (intraventricular hemorrhage, retinopathy of prematurity, bronchopulmonary dysplasia, necrotizing enterocolitis), discharged with home oxygen, or with gastrostomy placement experienced increased utilization of PT, OT, and ST compared with peers. However, substantial variation in service utilization occurred by the state of enrollment and selected maternal characteristics.Conclusions ELGANs with severe medical comorbidities are more likely to utilize services after discharge. Therapy utilization may be impacted by maternal characteristics and state of enrollment. Outpatient therapy services remain significantly underutilized in this high-risk cohort. Further research is required to characterize and optimize the utilization of therapy services following NICU discharge of ELGANs.Key Points
Keywords: early intervention; extremely preterm; physical therapy; speech therapy; occupational therapy